ANALISIS DAN PENGUKURAN PARAMETER REAKTOR KARTINI UNTUK PENERAPAN METODE K0-NAA - Murniasih, Sri; ROto; Taftazani, Agus; M., Th. Rina; Sutisna (Jurnal Teknologi Reaktor Nuklir Tri Dasa Mega, 2015)
The k0-NAA method is an analysis method that widely used by many of the advantages. In the application of k0-NAA method needed valuea of reactor parameters (f and α), then the purpose of the research would be conducted measurement parameter values f and α in the Lazy Susan Kartini reactor facilities. The methods used include Cd-ratio and triple bare methods. The parameter value has been measured in three channels in the irradiation facilities Lazy Susan. Differences of measurement results obtained parameter values are significant in each channel irradiation, the value of ƒ ranged from 13.713 to 22.128 and the value of α ranged from -0.060 – 0.068. The results of measurements for the f and α with the Cd-ratio method, providing more stable value than the triple bare method. The value of f and α obtained can be used a database for the application of k0-NAA method for sample analysis in the laboratory NAA – CAST.